1989
DOI: 10.1002/ep.3300080313
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between laboratory and pilot‐scale combustion of some chlorinated hydrocarbons

Abstract: Environmental Progress is a publication of the American Institute of Chemicol Engineers. It will deal with multi-faceted aspects of the pollution problem. It will provide thorough coverage of abatement, control, and containment of effluents and emissions within compliance standards. Papers will cover all aspects including water, air, liquid and solid wastes. Progress and technological advances vital to the environmental engineer will be reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Calculations and experimental observations have shown that the emissions of undestroyed, residual POHCs are kinetically, not thermodynamically controlled, (i.e., thermodynamic equilibrium calculations predict emission rates 3-10 orders of magnitude less than observed) (3,(10)(11)(12)(13). Thus, under the assumption that heterogeneous reactions are insignificant and mass transport is not rate-limiting, POHC destruction in incinerators is controlled by gasphase chemical kinetic factors including temperature, reaction atmosphere, and residence time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations and experimental observations have shown that the emissions of undestroyed, residual POHCs are kinetically, not thermodynamically controlled, (i.e., thermodynamic equilibrium calculations predict emission rates 3-10 orders of magnitude less than observed) (3,(10)(11)(12)(13). Thus, under the assumption that heterogeneous reactions are insignificant and mass transport is not rate-limiting, POHC destruction in incinerators is controlled by gasphase chemical kinetic factors including temperature, reaction atmosphere, and residence time.…”
Section: Introductionmentioning
confidence: 99%
“…Humic acid (HA) solution may enhance the removal of NPOC from soil and aquifer systems because dissolved humic acid was previously found to increase the apparent water solubility of NPOC (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The increase in solubility in an aqueous system containing dissolved humic acid can be described by eq 1 (17):…”
Section: Introductionmentioning
confidence: 99%